2019
DOI: 10.4174/astr.2019.97.4.159
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant action of hypoxic conditioned media from adipose-derived stem cells in the hepatic injury of expressing higher reactive oxygen species

Abstract: PurposeAlmost all liver diseases are known to be accompanied by increased levels of reactive oxygen species (ROS), regardless of the cause of the liver disorder. However, little is known about the role of hypoxic conditioned media (HCM) in the view of pro-oxidative/antioxidative balance.MethodsNormoxic conditioned media (NCM) and HCM were obtained after culturing adipose-derived stem cells in 20% O2 or 1% O2 for 24 hours, respectively. Their effects on the expression of various markers reflecting pro-oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The necrotic area was significantly lower in the FOXA2-overexpressing ADSC/scaffold group than in the other groups ( Figure 7(c) , iii) [ 158 ]. ADSCs cultured in hypoxia-conditioned media induced higher expression of antioxidant enzymes and nuclear factor erythroid 2-like 2 (Nrf2), thereby protecting against reactive oxygen species-related toxicity in the injured liver [ 159 ]. Many clinical trials have been designed to confirm the efficacy and safety of ADSCs in patients with liver cirrhosis or ALF.…”
Section: Regenerative Medicine Based On Adscsmentioning
confidence: 99%
“…The necrotic area was significantly lower in the FOXA2-overexpressing ADSC/scaffold group than in the other groups ( Figure 7(c) , iii) [ 158 ]. ADSCs cultured in hypoxia-conditioned media induced higher expression of antioxidant enzymes and nuclear factor erythroid 2-like 2 (Nrf2), thereby protecting against reactive oxygen species-related toxicity in the injured liver [ 159 ]. Many clinical trials have been designed to confirm the efficacy and safety of ADSCs in patients with liver cirrhosis or ALF.…”
Section: Regenerative Medicine Based On Adscsmentioning
confidence: 99%
“…This alteration on preconditioned cells is also reported to be related to increases on secretome therapeutic potential. In non-CNS-related pathologies, secretome preconditioned in hypoxia from adipose stem cells (ASCs) is reported to improve recovery in a model of hepatic injury in both in vitro and in vivo, with upper regulation of enzymes with antioxidant properties [40]. In other injury scenarios, this preconditioning method of MSCs seems to potentiate the wound healing and regenerative process provided by the secretome [41][42][43] when delivering the total secretome or only the vesicular fraction [44,45].…”
Section: Collecting Proceduresmentioning
confidence: 99%
“…The observation that MSC secretome possesses antioxidant properties has also been proved in other contexts. In the injured liver, hypoxic conditioned media derived from adipose stem cells provided protection against ROS-related toxicity by increasing the expression of antioxidant enzymes, in part by releasing Nrf2 [159]. Bellei et al [160] recently demonstrated that secreted molecules, obtained from adipose tissue, ameliorated the ability to dampen oxidative stress through a rise on intracellular antioxidant enzymes that improved cell proliferation in dermal and epidermal vitiligo cells in vitro.…”
Section: Mesenchymal Stem Cells Potential In Neuronal Differentiationmentioning
confidence: 99%